2003
DOI: 10.1007/bf03178465
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in volume calculations between different radiotherapy treatment planning systems

Abstract: It has been determined that, contrary to expectation, there is a clinically significant variation in the volume calculations of different RTPS (Radiotherapy Treatment Planning System) for identical contours. The situation was investigated prior to a multi-centre trial 1 to determine whether tumour volume is an independent prognostic factor in NSCLC (nonsmall cell lung cancer) 2 and included four of the commercially available RTPS. The four RTPS tested were, Theraplan Plus V3.0, Cadplan V6.2, Focus V2.6 and ADA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 4 publications
2
31
0
Order By: Relevance
“…The information provided by the dose volume histogram is based on the definition of tumor and critical structures, and also on the accuracy of the calculation algorithms. The target volume definition is influenced by several parameters such as imaging modality, [9,10] interobserver variability, [11][12][13] patient movement/setup errors, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] resolution limitation of the scanner [17] and contouring system. [6] In this study, we have assessed the variation of tumor volume between different treatment planning systems and also compared the differences in generating PTV from CTV with different planning systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information provided by the dose volume histogram is based on the definition of tumor and critical structures, and also on the accuracy of the calculation algorithms. The target volume definition is influenced by several parameters such as imaging modality, [9,10] interobserver variability, [11][12][13] patient movement/setup errors, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] resolution limitation of the scanner [17] and contouring system. [6] In this study, we have assessed the variation of tumor volume between different treatment planning systems and also compared the differences in generating PTV from CTV with different planning systems.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that there is a significant difference between the volumes computed by the treatment planning systems. [5,6] Currently, Dicom objects are widely used in radiotherapy as a standard protocol for transferring images and RT datasets. We have multiple treatment planning systems in our department and the usual methodology is to contour the structures in one treatment planning system/contouring station and transfer the images to other treatment planning system depending on the workload.…”
Section: Introductionmentioning
confidence: 99%
“…All institutions submitted the dry run planning results, but only the datasets with complete DICOM RT files (RT plan, structure, and dose) available at the time of analysis (this included eleven plans for Case1 and seven plans for Case2) were qualified for this study. The volumetric and dosimetric parameters for the same plan calculated by different software systems may differ [18]. Therefore, all submitted plans were imported into a single software system, MIMvista (Version 5.2.1; MIMvista Corp., Cleveland, OH), for consistent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The structure is automatically expanded from the boundary slices 1 /2 CT slice width inferiorly and superiorly. 10 This was verified by computing the volumes of axially aligned cylinders with different axial contour spacings. Other than that, the details of the DVH calculation algorithm are not documented in public domain.…”
Section: A2 Pinnaclementioning
confidence: 99%